Genetic toxicity of water contaminated by microcystins collected during a cyanobacteria bloom - Pamplona-Silva, Maria Tereza [UNESP]; Gonçalves, Letícia Cristina [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Elsevier, 2018)
Microcystin-LR (MCLR) is a toxin mainly produced by Microcystis aeruginosa, cyanobacteria most commonly found in eutrophic environments. Cyanobacteria blooms have affected Salto Grande reservoir (Americana, State of São Paulo/Brazil) for several decades, often observed during periods of drought. In this study, the genotoxic effects of MCLR (95% purity) and water samples contaminated by this toxin were evaluated during cyanobacteria bloom using assays with the test organism Allium cepa. The results showed genotoxic action for pure microcystin and cytotoxic, genotoxic and mutagenic action for water samples collected during flowering. Chromosomal aberration assays have shown that MCLR induces chromosomal breaks that persist in the daughter cells as MN. Therefore, it is possible to infer a clastogenic action for this toxin. The MCLR present in the environmental samples was shown to be more cytogenotoxic for the cells than the different concentrations tested in this study with the pure substance. This amplified toxic action can be related to a synergistic effect between the MCLR and other compounds present in the environmental samples. The genotoxicity studies with MCLR show inconsistent and inconclusive results, so this toxin needs to be better investigated in order to obtain further information about the action mode of it is on the biological system.
Keywords: Allium cepa; Cell death; Chromosomal aberration; Cyanotoxin; Micronuclei